Esm Method and Laplace Transform of Klafter-Bluken Equation for Det Analysis in Polyker Blend Like Naterials. - Pekcan, önder (Springer Science and Business Media LLC, 1992)
AbstractFluorescence decay curves from particles composed of poly(vinyl acetate) (PVAc) and naphthalene (N) labelled poly (2-ethylhexyl methacrylate) (PEHMA) were analyzed for Direct Energy Transfer (DET) from N to anthracene by the exponential series method(ESM). An averaged apparent dimension of d=2.0 were observed. The Laplace transformed Klafter-Blumen(KB) equation for the lifetime distribution was used to interpret these dimensions. Additional fluorescence experiments were carried out on Polymer films composed of the same material above. Exposure of the films to a pentane solution of 9-anthrylmethyl pivalete (AMP) transferred the AMP molecules exclusively to the PEHMA phase of the material. ESM analysis together with transformed KB equation showed that PEHMA thread has a unique dimension of 1.3 in PVAc matrix of this polymer film.